2018
DOI: 10.1016/j.bja.2018.02.067
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of transport in a toy car for reducing preoperative anxiety in preschool children: a randomised controlled prospective trial

Abstract: ChiCTR-IOR-17012791.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
3
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 34 publications
1
37
3
8
Order By: Relevance
“…A recent randomized controlled study demonstrated that riding in a toy car significantly reduced preoperative anxiety compared with riding on a stretcher among children with or without premedication, which was consistent with our results [12]. Interestingly, the anxiolytic effect of riding in a toy car was similar to that of oral midazolam, even just before anesthesia induction in the previous study [12]. These favorable results may have been due to the age range of the study population (2-5 years), which corresponds to the younger children in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent randomized controlled study demonstrated that riding in a toy car significantly reduced preoperative anxiety compared with riding on a stretcher among children with or without premedication, which was consistent with our results [12]. Interestingly, the anxiolytic effect of riding in a toy car was similar to that of oral midazolam, even just before anesthesia induction in the previous study [12]. These favorable results may have been due to the age range of the study population (2-5 years), which corresponds to the younger children in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Until recently, however, this simple method has not been evaluated through clinical trials. Only a very recent study by Liu et al [12] compared the anxiolytic effect of transport in a children's toy car to that in a conventional transport vehicle, and favorable results were obtained in children aged 2-5 years. However, there is still limited evidence to support the effect of the transport method on reducing preoperative anxiety among children, and furthermore, it is not clear whether this anxiolytic effect varies according to the age of the children.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial from China that used the same assessment tools as we did enrolled children aged 2 to 5 years undergoing their rst corrective surgery for congenital heart disease [15]. The children in the intervention group were taken to the operating room in a manual toy car pushed by an orderly, instead of being transported supine on a gurney.…”
Section: Discussionmentioning
confidence: 99%
“…Distraction with a hand-held video game or electronic tablet decreased preoperative anxiety to a greater extent than did midazolam [13,14]. The toy-car is a recent tool whose impact on child anxiety has been little studied [15]. This playful tool involves the child through play, like the other distracting tools currently available, but also makes the child an actor of his own care.…”
Section: Introductionmentioning
confidence: 99%
“…18 Additionally, research on nonpharmacologic preoperative anxiolytic techniques (eg, transporting patient in a toy car, video distraction), has shown promising results. [19][20] While midazolam administration can improve pediatric anxiety preoperatively, other adjunctive anxiolytic techniques can also be useful in this setting. 21,22 The incidence of use of midazolam as a premedication cannot be clearly ascertained.…”
Section: Discussionmentioning
confidence: 99%